Evaluation of different methods in quantification of manufacturing defects - Hien, Bui Minh; Sergent, A.; Villeneuve, F. (Applied Science and Engineering Progress, 2013)
In the context of manufacturing defects, our interest is the calculation methodologies that are used to quantify these defects. The manufacturing defects can be divided into two categories: machining defects and positioning defects. A double measurement method is principally used to quantify separately machining and positioning defect. The first measurement is operated inside a machine tool just after the final cutting step. The second measurement is realised outside of the machine tool (e.g. on a coordinate measuring machine - CMM). However, data processing method and precision between two different machines are different. Consequently, the measurement results obtained from these machines may be not comparable to quantify precisely the manufacturing defects. Several solutions are proposed and analysed in this paper to estimate comparable capability of the measurement results obtained by the two different measurement means